Intraoperative rescue of a dislodged renal stent during fenestrated endovascular aortic repair for treatment of type 1A endoleak - Mario D’Oria, MD; Filippo Griselli, MD; Cristiano Calvagna, MD; Sandro Lepidi, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
In the past 15 years, fenestrated-branched endovascular aortic repair (F-BEVAR) has progressively become the first-line option for management of most complex abdominal aortic aneurysms (AAAs); with increasing experience, as well as persistent technological refinements, F-BEVAR indications have been expanded to include rescue of failures after prior EVAR. Despite the feasibility and effectiveness, F-BEVAR procedures in the presence of prior infrarenal endografts may come with higher technical complexity that should be properly anticipated, and several anatomical challenges can be expected. Among these, presence of suprarenal bare stents from prior EVAR device are certainly a frequent scenario and may sometimes make target vessel cannulation more difficult because of encroachment on the target vessel origins. In this manuscript, we report a case intraoperative rescue of a dislodged renal stent during FEVAR for treatment of type 1 endoleak with the aim of showing the culprit of the complication, how to recognize it, and the off-label solution that was devised to solve it.